Comparison of the different methods of width estimation in unerupted canine and premolars - Tania Ghasemi; Morteza Sabbaghzadeh; Melika Mollaei; Maysam Mirzaei (BMC, 2024)
Abstract Background There are different methods for determining the required space for unerupted teeth. However, the accuracy of these techniques varies depending on ethnic differences. Therefore, the current study was performed to compare the accuracy of four methods for estimating the mesiodistal width of unerupted canines and premolars in a population of northern Iran. Methods The present cross-sectional study was conducted on 50 pairs of dental casts of patients aged 12-24 years old. The mesiodistal width of the teeth was measured with a digital caliper by two observers (ICC < 0.9), and the mean value was recorded. The space required for eruption of canines and premolars was obtained by the Tanaka-Johnson formula and the Moyers tables and compared with the actual value by paired t test. Results The Tanaka-Johnson formula had overestimation in the maxilla and mandible, which was statistically significant (p < 0.001). The values obtained from the Moyers tables in different confidence levels were not accurate. However, the 65% level for the mandible had almost no difference from the actual value (P = 0.996 and r2 = 0.503). Furthermore, linear regression was obtained based on the total mesiodistal width of the maxillary first molar and mandibular central incisor (maxilla: Yx= 0.613X + 2.23 and mandible: Ym= 0.618X + 1.6) and the total mesiodistal width of the mandibular first molar and maxillary central incisor in each jaw (maxilla: Yx = 0.424X + 5.021 and mandible: Ym = 0.447X + 3.631). Conclusion The Tanaka-Johnson method was overestimated in the population of northern Iran. The 85% and 75% confidence levels of the Moyers table have the best clinical results for the maxilla and mandible, respectively. Regression based on maxillary first molars and mandibular central incisors has better results.